Interpreting the Elements of Halal Tayyiban into Regional Development: The Case of the Siak Regency - Loekman, Agus Suyitno; Perdana, Firdaus Fanny Putera (Sekolah Tinggi Manajemen IPMI, 2024)
This paper examines the integration of Halalan Tayyiban principles within the sustainable development policies of Siak Regency, Indonesia. The regency was recognized as a